Amadeus - Forman, Milos; Abraham, F. Murray; Hulce, Tom, 1953-; Berridge, Elizabeth, 1962-; Callow, Simon, 1949-; Dotrice, Roy, 1923-2017; Ebersole, Christine; Jones, Jeffrey, 1947-; Kay, Charles, 1930-; McMillan, Kenneth, 1932-1989 (Warner Home Video, 2002)
Η ταινία παρουσιάζει την πολυτάραχη ζωή του μεγαλοφυιούς συνθέτη Μότσαρτ.